Correlation Between Head Nurse Supervision And Handover Implementation In Inpatient Ward RSUD Petala Bumi Riau Province: Hubungan Supervisi Kepala Ruangan Dengan Pelaksanaan Handover Di Ruangan Rawat Inap RSUD Petala Bumi Provinsi Riau 2018 - Susi Erianti; Rani Lisa Indra; Beni Sepila (STIKes Hang Tuah Pekanbaru, 2019)
Handover was a communication that accurred at the trun of shift, which had the purpose of communicating infformation about the state of the patient on previouse nursing care. If handover was not carried out properly it could lead to undesirable things (KTD). This research aimed to know the supervisory relationship between head of the room and handover practice. The study was quantitative research with correlation method and cross sectional design. Samples of this study were 40 people that taken using total sampling technique. The data were analyzed in univariat and bivariate, univariate used frequency distribution and bivariate used chi square test. The results showed that 85% were female, 57,5% were D III, 92,5% on 3rd level were (>5 years), 92,5% were absence of ward training, 57,5% of respondents stated that supervisory relationship was good, 60,0% of respondents handover implementation was not appropriate SOP and there was a significant relationship between the head of the room with handover implementation (p =0,013<0,05). It was expected that the hospital management paid more attention to the nurse’s work to match the existing SOP.